(untitled) (Journal of Governance and Development (JGD), 2021)
This article, drawing data from library and online sources, examines and engages issues in Africa’s quest for pax-Africana in the age of interventionism. It notes that Africa’s quest for pax-Africana in the age of interventionism is undercut by many factors, chief among which is the dependency and weaknesses of African states which always predispose extra-African powers to intervene in matters that should exclusively be handled by Africans. It concludes that as long as Africa remains trapped in dependent relations and the climate of disunity persists among African statesmen, its quest for pax-Africana would remain daunting.